Clustering Vaksinasi Penyakit Mulut dan Kuku Menggunakan Algoritma Fuzzy C-Means - Yusril Hidayat; Alwis Nazir; Reski Mei Candra; Suwanto Sanjaya; Fadhilah Syafria (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Foot and Mouth Disease is a disease that attacks cloven hooves, this disease spreads very quickly and the mortality rate of infected animals is up to 100%. FMD is caused by type A picornaviridae virus, namely Apthaee epizootecae, which has a development period of 1-14 days after the animal is infected. The delay in handling it can cause many livestock to die and have an impact on cattle farmers. One of the steps taken to prevent the spread of this disease is to eradicate all livestock. The Riau Provincial Government has taken steps to prevent vaccination of all livestock in Riau Province in the form of preventing this disease from becoming more widespread. From these problems, this research will form a data cluster for the PMK program in Riau Province so that the government can improve supervision of livestock to prevent re-outbreaks of foot and mouth disease in Riau Province. The method used is data mining with the Fuzzy C-means algorithm and the data used comes from the Department of Animal Husbandry and Animal Health in Riau Province. The best cluster results after testing is 2 clusters. The most numerous clusters are in cluster 1 with a total of 48704 cows and cluster 2 with a total of 21232. The validity test using the DBI gets a value of 0.416, so it is still far from good